Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1001/jamadermatol.2013.10526
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Phosphodiesterase Inhibitor (Apremilast) for Inflammatory Rosacea in Adults: A Pilot Study

Abstract: treatment. Although the primary end point of papule and pustule count did not reach statistical significance, other important measures of improvement were statistically significant. The limitations of this study include the small sample size and the absence of a control arm. Apremilast may represent a novel alternative treatment for rosacea and rosacea-associated erythema. Larger randomized clinical studies are needed to more adequately evaluate the drug's efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…An open-label trial investigated the use of apremilast 20 mg BID for the management of erythematotelangiectasia (ETR) and papulopustular (PPR) rosacea among 10 participants with moderate to severe disease. 61 By 12 weeks, there was a significant decrease in PGA, ETR rating overall erythema, and nontransient erythema with the latter two persisting for 1 month after discontinuation of therapy. No difference was found in number of papules/pustules at the end of the study versus baseline.…”
Section: Rosaceamentioning
confidence: 88%
See 2 more Smart Citations
“…An open-label trial investigated the use of apremilast 20 mg BID for the management of erythematotelangiectasia (ETR) and papulopustular (PPR) rosacea among 10 participants with moderate to severe disease. 61 By 12 weeks, there was a significant decrease in PGA, ETR rating overall erythema, and nontransient erythema with the latter two persisting for 1 month after discontinuation of therapy. No difference was found in number of papules/pustules at the end of the study versus baseline.…”
Section: Rosaceamentioning
confidence: 88%
“…No difference was found in number of papules/pustules at the end of the study versus baseline. 61 Overall, apremilast was well tolerated with only 2 urinary (UTI) and upper respiratory tract (URI) infections neither of which necessitated dose decrease or drug withdrawal. 61 Vitiligo A RCT investigating apremilast and narrowband ultraviolet B (nbUVB) phototherapy for the management of vitiligo failed to meet its primary endpoint and found no significant difference at either 24 or 48 weeks between vitiligo area and severity index (VASI) score, vitiligo extent score (VES), vitiligo European task force (VETF) score, or DLQI between apremilast and nbUVB and placebo and nbUVB.…”
Section: Rosaceamentioning
confidence: 94%
See 1 more Smart Citation
“…20,21 A study that used indirect methods of comparison to analyze the comparative cost and efficacy of apremilast and methotrexate found no evidence of greater efficacy for apremilast and that the incremental cost to achieve 1 additional PASI-75 responder by using apremilast is $187,888 annually. 21 Psoriatic Arthritis-The PALACE clinical trials 1, 2, and 3 assessed the efficacy of apremilast in patients who Evidence for Off-Label Use of Apremilast [24][25][26][27][28][29][30][31][32] Condition Evidence for apremilast AD Phase 2 RCT of adults with moderate to severe AD showed a 15%-20% improvement in the EASI score, with a slight advantage when using higher (40 mg twice daily) dosing 24 Open-label pilot study of 16 adult patients showed notable improvement in EASI, itch VAS, and DLQI; 50% (5/10) of patients treated for 6 mo improved ≥1 point on the IGA scale at 30 mg twice daily dosing 25 Open-label trial of 10 patients with AD and allergic contact dermatitis found that apremilast 20 mg twice daily was minimally effective in AD but well tolerated, with 20% (2/10) of patients improving by ≥2 points on the IGA scale and 10% achieving EASI-75 (ie, ≥75% reduction from baseline EASI score) 26 HS Small RCT of 20 patients with moderate HS who were treated for 16 wk with apremilast 30 mg twice daily found that 53% (8/15) in the treatment arm had clinically meaningful but not statistically significant improvement in pain, itch, and lesion count 27 Open-label phase 2 study of 20 patients with mild to moderate HS receiving apremilast 30 mg twice daily found that 65% (13/20) achieved a ≥50% reduction in the inflammatory lesion count on the HiSCR end point and notable improvement in pain and QOL 28 Lichen planus Small open-label trial of 10 patients with biopsy-proven lichen planus taking apremilast 20 mg twice daily found that 3 patients achieved the primary end point of improvement of ≥2 points in the PGA score from baseline to week 12; improvement in several other secondary end points related to QOL was noted 29 Rosacea Small open-label trial of 10 patients with moderate to severe erythematotelangiectatic and papulopustular rosacea taking apremilast 20 mg twice daily showed no significant difference between baseline pustule count and pustule count after 12 wk of therapy; there was significant improvement in several secondary end points related to QOL (PG-7A [P=.02], POES [P=.001], erythematotelangiectatic rating [P=.005]) 30 Alopecia areata Double-blind, placebo-controlled, single-center pilot study in 30 moderate to severe alopecia areata patients (≥50% scalp involvement) that were randomized 2:1 to receive apremilast (n=20) or placebo (n=10) orally for 24 wk (30 mg twice daily); no s...…”
Section: A B C F E Dmentioning
confidence: 99%
“…Los resultados se publicaron en 2014 27 : se detectó una mejoría estadísticamente significativa en las escalas generales Physician Global 7-point Assessment, Patient Global Assessment y en las de gravedad de la rosá cea eritemato-telangiectá sica (Physician Overall Erythema Severity, Erythematotelangiectatic Rating y en el eritema no transitorio), pero no en el nú mero de lesiones papulopustulosas. La mejoría en la escala Physician Global 7-point Assessment, Patient Global Assessment y en el eritema no transitorio se mantuvo hasta un mes despué s de suspender el tratamiento.…”
Section: Rosáceaunclassified